2010
DOI: 10.1007/bf03216931
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork — teach me, teach me not: A case study of three Australian preservice teachers

Abstract: Explicit training in teaming skills (both preservice and inservice) has been identified as a key means of facilitating the effective functioning of teaching teams (Main, 2007). This case study explored how groupwork tasks within university coursework can prepare preservice education students to work effectively in teaching teams. Three students in their final year of study were primed to the skills that have been identified as necessary for successful team practices. The students then participated in a semistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…In the ield of education, Main (2010) found that teachers' isolation is one of the hurdles that hinder the achievement of the goals and objectives of the school. Isolation with others prevents teachers from exchanging ideas with others that are vital in widening their skills and performing their duties and responsibilities successfully.…”
Section: Teamworkmentioning
confidence: 99%
“…In the ield of education, Main (2010) found that teachers' isolation is one of the hurdles that hinder the achievement of the goals and objectives of the school. Isolation with others prevents teachers from exchanging ideas with others that are vital in widening their skills and performing their duties and responsibilities successfully.…”
Section: Teamworkmentioning
confidence: 99%
“…Када говоримо о тимском раду наставника, можемо рећи да је он заступљен у организационим, саветодавним, административним пословима наставника, у оквиру пројеката и слично, док се у оквиру наставних активности јавља ретко и спорадично. Наставници најчешће раде индивидуално, независно од колега, самостално у својим учионицама (Main, 2010). Размена (мишљења, искустава, ставова) и дељење ресурса углавном се одвијају повремено.…”
Section: уводunclassified
“…Да би искористили потенцијале тимског рада, наставници претходно треба да познају погодности које колаборативна пракса и истинска колегијалност дају и тек онда да практикују тимски рад (Murata, 2002). Тимски рад у образовању треба да буде подупрт разумевањем његових теоријских основа, као и одговарајућим вештинама и обуком за његово планирање и реализацију (Main, 2010).…”
Section: уводunclassified
See 1 more Smart Citation
“…It moves away from the traditional idea that professionalism is a matter of professionals treating complex cases individually (Noordegraaf, 2015). The education system has been characterized by this traditional approach to professionalism for decades, with teachers working in relative isolation from other teachers within a classroom (Main, 2010). Both the physical structures of most school buildings and the cultural-historical norms of schooling have created a 'culture of isolation' in education, in which the opportunities for teachers to engage in professional dialogues are limited (Rogers & Babinski, 2002).…”
Section: Systemic Approach To Professionalismmentioning
confidence: 99%